Answer:
is their any way I can get some more info on this problem
Step-by-step explanation:
Answer:
steps below
Step-by-step explanation:
y = (x-3) / x
replace x and y: x = (y-3) / y
y - 3 = xy
y - xy = 3
y(1 - x) = 3
y (f'(x)) = 3 / (1-x)
Answer:
2x + 3 )(x + 2 )
Step-by-step explanation:
2x² + 7x + 6
Find two numbers multiplied together to get 6
and if you multiply one by 2, the answer is 7:
Tested:
6 & 1 but 6 · 2 + 1 = 13 or 6 + 2 · 1 = 8 No
2 & 3 and 2 · 2 + 3 = 7 Yes
2x² = 2x & x
all signs are positive
trinomial factoring ( )( )
( + )( + )
2 and 3 are the numbers to use (2x + 3 )(x + 2 ) or (2x + 2) (x + 3)
The largest number goes with the 2x.
Therefore (2x + 3 )(x + 2 )
Check 2x(x + 2) + 3(x + 2)
2x² + 4x + 3x + 6
2x² + 7x + 6 checked
Answer:
(3,4.5) is the answer. I am typing random things because it needs 20 characters. Monday morning and still have a it's super loud and still is not the same as you